2015
DOI: 10.5433/1679-0359.2015v36n4p2671
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors related to resistance to Rhipicephalus (Boophilus) microplus and weight gain of heifers

Abstract: The aim of the present study was to evaluate the influence of age and genetics in dairy heifers on resistance to the cattle tick Rhipicephalus (Boophilus) microplus and correlate these parameters with weight gain. Twenty-two heifers were evaluated from birth up to two years of age. Resistance to the cattle tick was evaluated by counting the number of engorged female ticks and subjective qualification of the larvae and nymph infestation. The animals were weighted in the first 24 hours after birth and at six, 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The animals were grouped into four categories (no infestation, low, intermediate, and high infestation) based on the tick infestation level and subjective qualification of the larvae and nymph infestation (Da Silva et al 2015). Since the genetic background of the animals could influence the natural resistance against tick infestation, the breeds/genetic group was considered the genetic factor in the present study.…”
Section: Counting Of Ticksmentioning
confidence: 99%
See 1 more Smart Citation
“…The animals were grouped into four categories (no infestation, low, intermediate, and high infestation) based on the tick infestation level and subjective qualification of the larvae and nymph infestation (Da Silva et al 2015). Since the genetic background of the animals could influence the natural resistance against tick infestation, the breeds/genetic group was considered the genetic factor in the present study.…”
Section: Counting Of Ticksmentioning
confidence: 99%
“…Furthermore, there are within-and between-breed variations in host resistance and purebred zebu is resistant to tick infestation (Kelley 1932). Several studies have suggested that Bos indicus (B. indicus) breeds and their crosses are more resistant than taurine breeds (Utech and Wharton 1982;Jonsson et al 2008;Ibelli et al 2012;Da Silva et al 2015;Lew-Tabor et al 2017). Factors like age, pregnancy, lactation status, sex, season, temperature, and humidity, as well as skin parameters like skin thickness, hair length, and coat score influence host resistance against ticks in cattle ( Utech et al 1978;Utech and Wharton 1982;Verissimo et al 1997Verissimo et al , 2002Jonsson et al 2000;Hughes and Randolph 2001;Webb and David 2002;Foster et al 2007;Gasparin et al 2007;Silva et al 2010;Ibelli et al 2012;Singh and Rath, 2013;Da Silva et al 2014, 2015.…”
Section: Introductionmentioning
confidence: 99%